Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/ppa.13443
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic approaches for plant disease control: Status and prospects 2021

Abstract: Plant diseases are responsible for major crop losses and postharvest spoilage; though losses are difficult to calculate, educated estimates suggest they are responsible for 20% to 40% of losses from plough to plate for major crops (Oerke, 2006;Savary et al., 2019). Hypothetically, with current estimated population growth, we could solve the challenge of feeding the world by 2050 were we able to control all disease (Collinge et al., 2010). Plant disease can be managed primarily by farmer skill, pesticides, dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 144 publications
0
19
0
1
Order By: Relevance
“…Both can be achieved by reducing inputs per unit of production (e.g., watering, spraying pesticides and applying inorganic fertilizers) and reducing food and fodder spoilage after harvest. Disease resistance is also an important means of disease management but effective resistance is often not available, whether introduced by conventional means (plant breeding) or biotechnologically by genetic engineering including new genomic technologies (Collinge & Sarrocco, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Both can be achieved by reducing inputs per unit of production (e.g., watering, spraying pesticides and applying inorganic fertilizers) and reducing food and fodder spoilage after harvest. Disease resistance is also an important means of disease management but effective resistance is often not available, whether introduced by conventional means (plant breeding) or biotechnologically by genetic engineering including new genomic technologies (Collinge & Sarrocco, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Within the strategies available to manage FHB and reduce the risk of mycotoxins entering the food chain, biological control by beneficial microorganisms such as bacteria, yeasts, and filamentous fungi, is receiving increasing attention due to pressure to reduce the use of pesticides and as an alternative to transgenic plants in those countries where their use is not allowed (Collinge and Sarrocco, 2022). Furthermore, other currently available tools for FHB management, such as agronomic practices, fungicides, and resistant wheat varieties, do not assure complete control of the disease (Sarrocco and Vannacci, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Plant disease management employs several strategies involving chemical and biological control of pathogens; it may also involve the use of resistant or tolerant genotypes manipulated by both conventional and molecular breeding. Although several strategies using genetic engineering have been developed to obtain plant disease resistance (Collinge & Sarrocco, 2021), only a few studies have demonstrated the effective control of bacterial diseases (Sundin et al, 2016). Most disease‐resistant transgenic crops commercially available so far are resistant to viruses (ISAAA, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…using genetic engineering have been developed to obtain plant disease resistance (Collinge & Sarrocco, 2021), only a few studies have demonstrated the effective control of bacterial diseases (Sundin et al, 2016). Most disease-resistant transgenic crops commercially available so far are resistant to viruses (ISAAA, 2021).…”
mentioning
confidence: 99%